ENHANCING EFL LEARNERS’ MASTERY OF SIMPLE PRESENT AND PAST TENSE THROUGH THE MAKE A MATCH TECHNIQUE - Siti Nurhaliza; Eka Indah Nuraini; Arifah Mardiningrum; Dian Nashrul Munif (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
This study aims to assess the effectiveness of the Make a Match technique in improving EFL students’ mastery of simple present and simple past tense sentence structures. It employed a quasi-experimental design with a non-equivalent control group to test the impact of the technique on EFL students’ grammar performance. The participants consisted of 64 fourth-grade students at Pondok Modern Darussalam Gontor for Girls Campus 3, divided into an experimental group and a control group. Data were collected using pre-tests and post-tests instruments which had been validated and demonstrated high reliability (Cronbach’s Alpha=0.897). Nonparametric statistical techniques, such as the Mann-Whitney U test and the Wilcoxon Signed Rank test, were eventually used to analyze the data. The findings revealed that students in the experimental group improved far more than those in the control group. The effect size (r = 0.41) showed that the Make a Match method had a moderate to substantial impact on students' grammar competency. This study confirmed that the Make a Match method was practical relevance for EFL classrooms by greatly improving EFL students' grammatical accuracy and engagement of the simple present and simple past tenses. This work offers to the literature and has practical implications for teaching grammar in Islamic educational contexts through cooperative learning methodologies.